Career adaptability profile of FKIP ULM guidance and counseling students - Ali Rachman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Career adaptability as a construct that can predict career development shows flexibility or desire to fulfill career tasks. This study aims to find out how the general description of the career adaptability profile for Guidance and Counseling study program students at Lambung Mangkurat University class of 2016. This study uses a quantitative approach with a descriptive type. The number of students in the study who became the research subjects was 72 in the BK FKIP ULM Banjarmasin Study Program. The topics in this study used saturated sampling. Data collection uses scale the career adaptability instrument from Sarvick. The data analysis technique used in this research is descriptive statistical analysis. The results of the study show that 29% of students in the Guidance and Counseling Study Program FKIP ULM are in the category of the strongest career adaptability, 65% in the very strong category, 6% in the strong category, and 0% in the rather strong and not strong category. The results of this study also found that the category of very strong career adaptability in male students was higher than in female students.